Sistem Pendukung Keputusan Pemilihan Lahan Tanaman Kopi Menggunakan Metode Complex Proportional Assessment (COPRAS) - Ahmad Fathurrozi; Amat Damuri; Agung Tri Prastowo; Yuri Rahmanto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Land is one of the important aspects in cultivating coffee plants. This is because the land has a stake in increasing the quality and yield of crops. To select a coffee field, it is necessary to be based on accurate data and information about the land. So, conventional decision-making will take time because it needs to be discussed and compared between data from one field to another. So, the purpose of the research conducted is to develop a Decision Support System (DSS) using the Complex Proportional Assessment (COPRAS) method to determine the right coffee area and according to needs. The COPRAS approach can carry out different alternative analyzes and is able to make alternative estimates that are adjusted to the level of utility by providing ratings presented in intervals. Based on a case study conducted using the COPRAS method, the highest utility value was land in Banjar Negeri Village (A2) with a value of 100, followed by Tanjung Agung Village (A3) with a value of 93.64, Tanjung Jati Village (A1) with a value 92.90 and Kampung Baru Village with a value of 83.53. The results of the SPK developed with the results of manual calculations get the same value. Besides that, the test through Black-Box Testing shows the results that all system functions built can run well